Antifungal Activity of Seaweed Agains Aspergillus flavus - K.S.M Julyasih; A. Purnawati (Future Science)
Various types of fungi such as Aspergillus flavus attack a lot of food items after harvest, these fungi can produce aflatoxin which is very toxic to consumers. Aflatoxin cannot be neutralized through cooking so efforts to avoid fungal contamination need to be done.The use of synthetic chemicals as a controller of fungal growth in foodstuffs can have adverse effects on health, so it needs natural control ingredients that do not have an impact on human health. One of the natural mushroom controllers is by utilizing natural resources, including seaweed. Processing of seaweed as an antifungal is an alternative that needs to be realized. For this reason, it is necessary to examine the inhibitory activity of several types of seaweed against A. flavus. This study examined several types of seaweed that have the potential effect to inhibit the development of A. flavus. The results showed that Caulerpa racemosa seaweed has a very strong inhibitory ability compared to other types of seaweed.